Meningkatkan Kemandirian Dalam Pembelajaran Pak Melalui Model PBL Berbantuan Media Video Materi Laki-Laki Dan Perempuan Kelas VIII SMP Pl Santo Albertus Ketapang - Gergorius Menue Raya Demon (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This study aims to increase student learning independence in learning Catholic Religious Education with the Problem Based Learning model assisted by video media at SMP PL Santo Albertus grade VIII. improve critical thinking skills in learning Catholic Religious Education with the Problem Based Learning model assisted by video media at SMP PL Santo Albertus class VIII. The methodology used in this study is a quantitative descriptive research methodology and literature review. This classroom action research consisted of two cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. The results of this study indicate that the application of the Problem Based Learning learning model can increase students' independence and critical thinking skills. This is indicated by an increase in independent learning. The results of cycle 2 showed an increase from cycle 1. The indicator asking did not understand was 31.89 at the end of cycle 1 and after cycle 2 was 76.66. The indicator of doing the task is 42.70 at the end of cycle 1 and after cycle 2 is 83.33. The active indicators answered questions at 26.48 at the end of cycle 1 and after cycle 2 at 72.77. The indicator of having the initiative to make notes was 40.0 at the end of cycle 1 and after cycle 2 it was 82. On the indicator looking for relevant sources it was 51.89 at the end of cycle 1 and after cycle 2 it was 70.55. In critical thinking skills, students were not found to be in the proper category. There are 9 students proficient and 27 students proficient. This shows an increase in critical thinking skills.